The Role of MicroRNAs in Regulating Cytokines and Growth Factors in Coronary Artery Disease: The Ins and Outs. (25th July 2020) - Gorabi, Armita Mahdavi; Kiaie, Nasim; Sathyapalan, Thozhukat; Al-Rasadi, Khalid; Jamialahmadi, Tannaz; Sahebkar, Amirhossein
Abstract : Coronary artery diseases (CAD), as a leading cause of mortality around the world, has attracted the researchers' attention for years to find out its underlying mechanisms and causes. Among the various key players in the pathogenesis of CAD cytokines, microRNAs (miRNAs) are crucial. In this study, besides providing a comprehensive overview of the involvement of cytokines, growth factors, and miRNAs in CAD, the interplay between miRNA with cytokine or growth factors during the development of CAD is discussed.